(untitled) (Proceedings of International Conference on Educational Discoveries and Humanities, 2024)
In this article, the essence of neural networks, their current development and their connection with fields such as medicine, neurophysiology, psychology and architecture. The need and methods of these neural networks are described and analyzed. Also, by discussing the benefits or negative aspects of these neural networks that they bring to our life, lifestyle, it is possible to come to the correct conclusion about these neural networks.